Complex population structure of the Atlantic puffin revealed by whole genome analyses - Oliver Kersten (Nature Portfolio, 2021)
Kersten et al. sequence a draft genome for the Atlantic puffin and report its population structure, genetic diversity and gene flow among four main clusters of populations across the northern Atlantic. These results identify a secondary contact zone between the puffins from the High Arctic and other colonies and proposes a new population structure from the currently recognized three subspecies.